A nationwide survey of public healthcare providers’ impressions of family medicine specialists in Malaysia: a qualitative analysis of written comments - Chew, Boon-How; Cheong, Ai-Theng; Ismail, Mastura; Hamzah, Zuhra; A-Rashid, Mohd Radzniwan; Md-Yasin, Mazapuspavina; Ali, Norsiah; Mohd-Salleh, Noridah; Bashah, Baizury (BMJ Publishing Group, 2016)
Objective: To examine impressions of public healthcare providers/professionals (PHCPs) who are working closely with family medicine specialists (FMSs) at public health clinics. Design: Cross-sectional study. Setting: This study is part of a larger national study on the perception of Malaysian public healthcare professionals on FMSs (PERMFAMS). Participants: PHCPs from three categories of health facility: hospitals, health clinics and health offices. Main outcome measures: Qualitative analyses of written comments of respondents' general impression of FMSs. Results: The participants' response rate was 58.0% (780/1345), with almost equal proportions from each public healthcare facility. A total of 23 categories for each of the 648 impression comments were identified. The six emerging themes were: (1) importance of FMSs; (2) roles of FMSs; (3) clinical performance of FMSs; (4) attributes of FMSs; (5) FMS practice challenges; (6) misconception of FMS roles. Overall, FMS practice was perceived to be safe and able to provide effective treatments in a challenging medical discipline that was in line with the current standards of medical care and ethical and professional values. The areas of concern were in clinical performance expressed by PHCPs from some hospitals and the lack of personal attributes and professionalism among FMSs mentioned by PHCPs from health clinics and offices. Conclusions: FMSs were perceived to be capable of providing effective treatment and were considered to be important primary care physicians. There were a few negative impressions in some areas of FMS practice, which demanded attention by the FMSs themselves and the relevant authorities in order to improve efficiency and safeguard the fraternity's reputation.